PENGUJIAN TINGKAT KEMIRIPAN SKRIPSI MAHASISWA DENGAN ALGORITMA GENETIKA MENGGUNAKAN POSI FORMULATION - Darwis Robinson Manalu; Edward Rajagukguk (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Measures the percentage similarity becomes important documents today because of the many digital documents in particular scientific work. Measurements were performed by using keywords solution of some of the documents that the user selected after the competition keywords. The process of determining keywords algorithm solution with genetics to produce the latest generation of the best with Jaccard Function. Then the similarity calculation process will be done using the keyword query comparing the solution with an existing document in a database that is in the post title, abstract, keywords and references. Similarity calculation method used is the Percentage of Similarity (POSI) Formulation. The number of keywords found on each document will be distributed in the whole of keywords that are found to produce a percentage of similarity. From the tests results obtained similarity of documents idDoc-661 amounted to 32.26%, 24.19% in the second sequence idDoc-665 and the third number of 19.35% on idDoc-663 and fourth at 12.90% in idDoc -667 and the latter by 11.29% in idDoc-666. Based on these tests can find out similarities with the other documents.